Atrial fibrillation and rapid acute pacing regulate adipocyte/adipositas-related gene expression in the atria. (6th May 2015) - Chilukoti, R.K.; Giese, A.; Malenke, W.; Homuth, G.; Bukowska, A.; Goette, A.; Felix, S.B.; Kanaan, J.; Wollert, H.-G.; Evert, K.; Verheule, S.; Jais, P.; et al.
Abstract: Purpose: Atrial fibrillation (AF) has been associated with increased volumes of epicardial fat and atrial adipocyte accumulation. Underlying mechanisms are not well understood. This study aims to identify rapid atrial pacing (RAP)/AF-dependent changes in atrial adipocyte/adipositas-related gene expression (AARE). Methods: Right atrial (RA) and adjacent epicardial adipose tissue (EAT) samples were obtained from 26 patients; 13 with AF, 13 in sinus rhythm (SR). Left atrial (LA) samples were obtained from 9 pigs (5 RAP, 4 sham-operated controls). AARE was analyzed using microarrays and RT-qPCR. The impact of diabetes/obesity on gene expression was additionally determined in RA samples (RAP ex vivo and controls) from 3 vs. 6 months old ZDF rats. Results: RAP in vivo of pigs resulted in substantial changes of AARE, with 66 genes being up- and 53 down-regulated on the mRNA level. Differential expression during adipocyte differentiation was confirmed using 3T3-L1 cells. In patients with AF (compared to SR), a comparable change in RA mRNA levels concerned a fraction of genes only ( RETN, IGF1, HK2, PYGM, LOX, and NR4A3 ). RA and EAT were affected by AF to a different extent. In patients, concomitant disease contributes to AARE changes. Conclusions: RAP, and to lesser extent AF, provoke significant changes in atrial AARE. In chronic AF, activation of this gene panel is very likely mediated by AF itself, AF risk factors and concomitant diseases. This may facilitate the development of an AF substrate by increasing atrial ectopic fat and fat infiltration of the atrial myocardium.